The Importance of Family Law Against Women in Polygamy - Nur Rizki Maulida; Arya Putra Perdana; Eka Widyanti (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2022)
In Indonesia, regarding the relationship between husband and wife or marriage law based on monogamy. However, polygamous marriages in Islam are not prohibited and are accommodated by the government in the Marriage Law. In Indonesia, regarding the relationship between husband and wife or marriage law based on monogamy. However, polygamous marriages in Islam are not prohibited and are accommodated by the government in the Marriage Law. This research method is descriptive qualitative. Data obtained through literature review or literature study. The results of the research are that there are government efforts related to family law that handle or overcome cases that occur to women including wives in polygamy who experience domestic violence, and their rights are not fulfilled. Permission to polygamy by the Religious Courts can be granted if the husband's reason has fulfilled alternative reasons in accordance with the provisions of Article 4 paragraph (2) and the cumulative conditions listed in Article 5 paragraph (1) of Law Number 1 of 1974.